PROFIL KEMATANGAN KARIER SISWA TINGKAT XI SMA NEGERI 2 LEMBANG - Siti Fatimah, Diana; Irmayanti, Rima; Utomo, Prio (IKIP Siliwangi, 2025)
This research aims to determine the career maturity profile of level XI students at SMA Negeri 2 Lembang in 2024. The research method used in this research is descriptive quantitative with a survey research design. The research sample was 72 students from class XI majoring in Social Sciences. Data collection used was a career maturity questionnaire and analysis of research data using descriptive statistics. From the results of distributing student career maturity questionnaire profiles, it was found that 28% were in the very low category, 32% in the low category, 18% in the medium category, 14% in the high category and 8% in the very high category. So it can be concluded from the results obtained that 60% of students have low career maturity, this needs to be addressed immediately so that students can increase their career maturity so they are able to plan and make the right career decisions for their future. The implications of the results of this research are as reference material, both practical and theoretical, for guidance and counseling teachers or future researchers in the field of guidance and counseling related to planning career guidance programs in helping students achieve career development tasks.